2023
DOI: 10.3389/fimmu.2023.1146841
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral responses after second and third SARS-CoV-2 vaccinations in patients with autoimmune diseases treated with rituximab: specific T cell immunity remains longer and plays a protective role against SARS-CoV-2 reinfections

Abstract: BackgroundHumoral and cellular immune responses are known to be crucial for patients to recover from COVID-19 and to protect them against SARS-CoV-2 reinfection once infected or vaccinated.ObjectivesThis study aimed to investigate humoral and T cell responses to SARS-CoV-2 vaccination in patients with autoimmune diseases after the second and third vaccine doses while on rituximab and their potential protective role against reinfection.MethodsTen COVID-19-naïve patients were included. Three time points were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…In this context, the data on the cellular response to the COVID-19 vaccine in patients with IMIDs treated with rituximab are especially relevant, given the foreseeable negative effect on the humoral response due to its mechanism of action. As expected, a negative association between seroconversion rates to the COVID-19 vaccine and rituximab has been confirmed, identifying the interval between the last RTX infusion and the first vaccination, the number of peripheral B-cells and the immunoglobulin quantity among the related factors [50,51], while the cellular response seems to be preserved [52]. Intervals of 6 to 9 months between the last rituximab administration and COVID-19 vaccination appear to improve the humoral response, although pharmacokinetic studies suggest that the presence of B cells and/or rituximab in the blood predict seroconversion better than time since last infusion [50,51,53].…”
Section: Anti-cd20supporting
confidence: 71%
“…In this context, the data on the cellular response to the COVID-19 vaccine in patients with IMIDs treated with rituximab are especially relevant, given the foreseeable negative effect on the humoral response due to its mechanism of action. As expected, a negative association between seroconversion rates to the COVID-19 vaccine and rituximab has been confirmed, identifying the interval between the last RTX infusion and the first vaccination, the number of peripheral B-cells and the immunoglobulin quantity among the related factors [50,51], while the cellular response seems to be preserved [52]. Intervals of 6 to 9 months between the last rituximab administration and COVID-19 vaccination appear to improve the humoral response, although pharmacokinetic studies suggest that the presence of B cells and/or rituximab in the blood predict seroconversion better than time since last infusion [50,51,53].…”
Section: Anti-cd20supporting
confidence: 71%
“…Another group of immunocompromised patients are those affected by autoimmune diseases requiring immunosuppressive therapies. Even in these cases, steady T cell responses to SARS-CoV-2 vaccination have been found at levels similar to controls [22], and were found to be present after a booster dose, therefore appearing to be protective against subsequent reinfections.…”
Section: Corroborating Data From Autoimmune Immunosuppressed and Prim...mentioning
confidence: 75%
“…Other studies reported comparable results of impaired humoral immune response, including not only AAV patients, but large and diverse groups of individuals with autoimmune inflammatory rheumatic diseases [ 29 , 30 ]. Following mRNA booster vaccination, we and others have shown that neutralizing antibody activity is significantly increased in most AAV patients [ 31 , 32 , 33 ]. However, patients treated with the CD20 monoclonal antibody rituximab had severely limited humoral immune responses even after booster vaccinations and high breakthrough infection rates have been reported for this cohort [ 7 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is the lack of data on cellular immunity data after SARS-CoV-2 vaccination. Especially in some patients under rituximab therapy, it could be shown that in the absence of humoral immune response at least antigen-specific activation of cellular immunity was detected [ 18 , 32 , 54 ]. Nevertheless, it has been clearly demonstrated that neutralizing antibodies are considered highly predictive of protection against symptomatic SARS-CoV-2 infection [ 4 ].…”
Section: Discussionmentioning
confidence: 99%